Women Support Women: How Coastal Women in Demak Step Out from Poverty - Nastabilla, Diandra Masayu; Prakoso, Raihan Yogi; Alhafizh, Raihan Yahya (Jurnal Ilmu Ekonomi Terapan, 2022)
According to research carried out by the Central Java provincial government in 2019, there are 13,415 poor people in the Demak Regency coastal area, where most people are fishers. The unstable income and the tendency of a consumer lifestyle followed by the weakness in money management are the main factors of poverty. Moreover, the covid-19 pandemic also aggravated the poverty of the coastal communities of the Demak Regency. Unfortunately for the coastal communities of the Demak Regency, the role of women is less significant because of the dominance of roles and cultural trends of patriarchy by men. Based on this, the coastal women there initiated a Women Support Women movement. This study used qualitative descriptive methods and a series of interviews and observations in its data retrieval. This study focused on identifying the form of the movement and explaining the impact on coastal women in Demak Regency to break out of the cycle of poverty and patriarchal culture. The results showed that the Women Support Women movement consists of individuals to the community, community to individuals, and community to community. There are three main actors in this movement: Forum Demak Hijau, Puspita Bahari, and Mrs. Pasijah. With this movement, coastal women in Demak Regency are proven to be able to contribute financially to their families, decreasing the patriarchal culture, and creating a trickle-down effect on others.